Boron Neutron Capture Therapy for Cancer: Future Prospects in Indonesia - Bagaswoto Poedjomartono; Hanif Afkari; Edy Meiyanto; Alan Bangun; Yohanes Sardjono (Universitas Gadjah Mada, 2018)
Boron neutron capture therapy (BNCT) is a form of cancer therapy based on the interaction of low-energy thermal neutrons and boron-10 (10-B) to produce alpha radiation from He-4 and Li-7 with a high linear energy transfer. A beam of neutrons irradiates a boron drug injected into the tumor, resulting in the boron-injected cancer cells receiving a lethal dose of radiation with the surrounding, healthy cells being minimally affected. Two boron drugs have been used clinically in BNCT, boron sodium captate (BSH) and borophenylalanine (BPA), while a third, pentagamaboronon-0 (PGB-0), is currently under development in the Faculty of Pharmacy of Universitas Gadjah Mada, Indonesia. In Indonesia, there has been a growing interest in the study and use of BNCT to treat cancer, as this method is expected to be safer and more effective than traditional cancer treatment methods.